Theological and Biblical Foundations for Performance Ethics in Congregational Worship - Odiase, Rev. Yeside (Advances in Social Sciences Research Journal, 2023)
Changes in global trends are throwing up discordant views in Christian worship which requires a biblical-theological approach to maintain a balance. This paper advocates for the necessity of standard ethics that is guided by theological and biblical principles for congregational worship. These guiding principles entrenched in the Old and New Testaments are fundamental to meaningful worship. The article examines the meaning of performance ethics, the concept of congregational worship, biblical and theological concepts of performance ethics in worship and the concept of congregational music in worship. The paper concludes with the recommendation that congregational worship which includes church music should be guided by biblical principles underpinning actions, liturgy and disposition with robust performance ethics to enrich worship and glorify God.